PCR-detection rates of T. pallidum ssp. pallidum in swab samples from the Czech Republic (2004–2022): Combined RPR, IgM, and PCR tests efficiently detect active syphilis - Eliška Vrbová; Petra Pospíšilová; Eliška Dastychová; Martina Kojanová; Miluše Kreidlová; Daniela Vaňousová; Filip Rob; Přemysl Procházka; Alena Krchňáková; Vladimír Vašků; Radim Strnadel; Olga Faustmannová; et al. (International Journal of Medical Microbiology)
Syphilis is a multistage sexually transmitted disease caused by Treponema pallidum ssp. pallidum (TPA). This study analyzed clinical samples collected from patients with a diagnosed syphilis infection from 2004–2022, isolated in the Czech Republic. Mucocutaneous swab samples (n = 543) from 543 patients were analyzed, and from these samples, 80.11 % (n = 435) were PCR positive, and 19.89 % (n = 108) were PCR negative for TPA DNA. Swabs were more often positive when collected from syphilis patients in the primary and secondary stages, compared to the latent or unknown stage. There was no significant difference in PCR positivity between the primary and secondary stages (p = 0.099). In IgM-positive patients, a statistically significant association with PCR-positivity was found in samples from seropositive (p = 0.033) and serodiscrepant (RPR negative) patients (p = 0.0006). When assessing our laboratory-defined cases of syphilis, the RPR, IgM, and PCR tests were similarly effective (within the range of 80.1–86.1 %). However, parallel testing with these methods was even more effective, i.e., RPR + PCR was 96.1 % effective and RPR + IgM + PCR was 97.8 % effective. A combination of RPR + PCR, or a combination of all three tests (RPR, IgM, and PCR) can therefore be used to reliably detect active syphilis cases, including reinfections. Our findings show that the reverse algorithm for detecting syphilis could be substantially improved by adding IgM and PCR testing.